Oasis landscape: A valuable urban sustainability solution in arid lands. Case of Biskra, Algeria - Boudjellal Lazhar; Boudraa Hocemeddine; Djaghrouri Djamila; Bouafia Abderrazek (Glasnik Srpskog Geografskog Društva)
Over centuries, oases have been islands of survival and sources of human settlement. Nowadays, massive urbanization poses a direct threat to this ingenious ecosystem and generates intensely hot air. Under these conditions, achieving thermal comfort, especially in summer, constitutes a major challenge. The use of air conditioning has serious consequences on energy consumption and thus disrupts the elements of sustainability. This research aims to highlight the importance of landscape heritage by identifying and evaluating the contribution of oases to mitigating Ta (air temperature). Based on field measurements of Ta during the overheating period, a land use/land cover map was prepared, processed, and analyzed using ArcGIS software. The comparison between data recorded at stations located inside and outside the oasis showed the development of a cool island. The results demonstrate the beneficial role of vegetation density in thermal regulation, providing guidance for planning green cities in hot and dry climates.